Longitudinal changes of blood parameters and weight in inoperable stage III NSCLC patients treated with concurrent chemoradiotherapy followed by maintenance treatment with durvalumab - J. Guggenberger; S. Kenndoff; J. Taugner; L. Käsmann; B. Flörsch; C. Belka; C. Eze; F. Manapov (BMC Cancer, 2022)
Abstract Background Investigating dynamic changes in blood-parameters and weight in patients with locally advanced non-small cell lung cancer (NSCLC) receiving durvalumab maintenance therapy after chemoradiotherapy (cCRT). Laboratory outcomes were determined based on the number of durvalumab administrations received. Methods Twenty-two patients completed platinum-based cCRT followed by maintenance treatment with durvalumab. Different parameters such as hemoglobin (Hb), leukocytes, Lactate dehydrogenase (LDH), C-reactive protein (CRP), body weight and albumin were analyzed before cCRT, after cCRT, 3, 6, 9 and 12 months after starting durvalumab maintenance. Results Sixteen (72.7%) patients were male; twelve (54.5%) and fifteen (68.2%) patients had non-squamous histology and Union for International Cancer Control (UICC) stage IIIB-C disease, respectively. Median follow-up time was 24.4 months; 12- and 18-months- progression-free and overall-survival rates were 55.0% and 45.0 as well as 90.2 and 85.0%, respectively. During maintenance treatment Hb increased by 1.93 mg/dl (17.53%) after 9 months (p < 0.001) and 2.02 mg/dl (18.46%) after 12 months compared to the start of durvalumab (p < 0.001). LDH decreased by 29.86 U/l (− 11.74%) after 3 months (p = 0.022). Receipt of at least 12 cycles of durvalumab was beneficial in terms of Hb-recovery (Hb 6 months: 12.64 vs. 10.86 [mg/dl]; Hb 9 months: 13.33 vs 11.74 [mg/dl]; (p = 0.03)). Median weight change [kilogram (kg)] was + 6.06% (range: − 8.89 − + 18.75%) after 12 months. The number of durvalumab cycles significantly correlated with total weight gain [kg] (Spearman-Rho-correlation: r = 0.502*). Conclusion In the investigated cohort, no severe hematologic toxicity occurred by laboratory blood tests within 1 year of durvalumab maintenance therapy after cCRT for unresectable stage III NSCLC. Receiving at least 12 cycles of durvalumab appears to have a significant effect on recovery of hemoglobin levels and body weight.